IMPLEMENTASI MODEL PEMBELAJARAN “WISATA LOKAL” PADA GURU DI KABUPATEN PEKALONGAN - Eny Winaryati; Sri Haryani; Akhmad Fathurohman; Setia Iriyanto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The learning model "Local Tourism" is a model that closer the students to the surrounding environment or local potential in the region. Each region has local potential advantages of different regions. In addition to excellence, each region is also faced with a diversity of issues. Both require unequal strengthening and problem-solving techniques. This technique requires a knowledge, skills (psychomotor) and attitude response (affective) are diverse. This is the reason for the development of learning model "Local Tourism". This model has been implemented in elementary, junior high school, vocational and senior high school teachers in Pekalongan district. Implementation stage is the application phase of trial model in the field. Implementation stage is the stage of R & D post development stage. The results of this implementation obtained data that the model is effective to use.Keywords: implementation, local tourism, pekalongan district